Simultaneous Longitudinal Examination of Hopelessness, Thwarted Belongingness, and Perceived Burdensomeness as Predictors of Suicide Ideation. Issue 4 (11th August 2018) - Roeder, Kathryn M.; Cole, David A.
Abstract : Objective: Based on Beck's hopelessness model (Beck, Kovacs, & Weissman, Journal of the American Medical Association, 234, 1975, 1146) and Joiner's ( Why people die by suicide, 2005, Harvard University Press, Boston, MA) interpersonal theory of suicide, this study simultaneously examined three cognitive risk factors (hopelessness, thwarted belongingness, and perceived burdensomeness) as predictors of suicide ideation. Method: The study focused on high school and college students ( n s = 192 and 142, respectively), assessed twice 4 months apart. Results: When hopelessness, perceived burdensomeness, and thwarted belongingness were examined separately, each cognitive risk factor predicted future suicide ideation in both groups. When the three cognitions were tested simultaneously, none emerged as uniquely predictive of suicide ideation. A longitudinal, latent variable model suggested that a common factor underlying all three types of cognition significantly predicted suicide ideation. Furthermore, thwarted belongingness predicted both hopelessness and perceived burdensomeness over time. Conclusions: Results suggest ways that aspects of Beck's and Joiner's theories complement each other and could be combined to yield a more comprehensive understanding of cognitive factors associated with suicide ideation.